In situ phase behaviour of a high capacity LiCoPO4 electrode during constant or pulsed charge of a lithium cell. Issue 98 (21st November 2016) - Palmer, Michael G.; Frith, James T.; Hector, Andrew L.; Lodge, Andrew W.; Owen, John R.; Nicklin, Chris; Rawle, Jonathan
Abstract : The phase changes that occur during lithium extraction from LiCoPO4 under constant or pulsed current were studied using synchrotron X-ray diffraction. Abstract : The phase changes that occur during lithium extraction from LiCoPO4 in lithium half-cells were studied using synchrotron X-ray diffraction. The existence of two two-phase regions with an intermediate phase present was observed. Significant variations in the composition of the phases of nominal stoichiometry LiCoPO4, Li2/3 CoPO4 and CoPO4 resulted in unit cell volume variations. On current pulsing, lattice parameter shifts and phase recovery were directly observed.